Magnetic Properties of Dinuclear and Trinuclear Copper (II) Complexes - Babujyan, Hrachya
In this work, I present the synthesis, structural characterization, and magnetic properties of trinuclear and dinuclear antiferromagnetic copper (II) complexes. Different bridging ligands were employed to investigate the impact of exchange interactions on the magnetization behavior. Utilizing both experimental data and theoretical antiferromagnetic models, I analyze magnetization plateaus, magnetic susceptibility, and entanglement entropy. Notably, the results reveal distinct magnetization plateaus and saturation points, which correlate with variations in exchange interactions and ligand frameworks. Furthermore, I calculate the thermal logarithmic negativity of the complexes, highlighting quantum entanglement behavior at low temperatures. My findings emphasize the role of ligand design in tuning magnetic and quantum properties, paving the way for future studies on related antiferromagnetic systems. Additionally, I explore connections between the quantum magnetic properties of these copper complexes and radiation field calculations in waveguide systems, drawing parallels in mathematical modeling techniques and spectral analysis.
Keywords: Physics